Intim und respektabel Homosexualität und Freundinnenschaft in der deutschen Frauenbewegung um 1900 - Heinrich, Elisa (2022)
The women's movement was not only a place of political debate - a large number of activists spent most of their time among women. While "respectability" played a significant role in these circles the gradually growing distinction between homo- and heterosexual relationships - popularized by sexology since the second half of the 19th century - placed the intimate relationships within the women's movement into new normative contexts. Elisa Heinrich both examines the discursive negotiation of female homosexuality by women's activists and sheds light on the conditions and consequences of this significant transition.